Real versus nominal adjustment mechanism of the Malaysian money demand function: further evidence - Habibullah, Muzafar Shah (Universiti Utara Malaysia, 1992)
This article investigates the issue of real versus nominal adjustment specifications in the Malaysian money demand function. Performance of both specifications was subjected to several test, namely ; model specification money demand function for M1, M2 and M3 are not stable for the period 1962-1991. Our question is, does financial innovation during the period of 1979-1991 affected the stability of the Malaysian money demand function? A test on Gurley-Shaw hypothesis was done to answer the above question. However, our results suggests that financial innovation does not play a major role in affecting the Malaysian money demand function during the period under study.